2015
DOI: 10.1007/s13277-015-3908-y
|View full text |Cite
|
Sign up to set email alerts
|

YT521 promotes metastases of endometrial cancer by differential splicing of vascular endothelial growth factor A

Abstract: The malignancy of endometrial carcinoma (EC) largely results from its high invasive feature. The regulation of the mRNA splicing of vascular endothelial growth factor A (VEGF-A) is critical for EC-associated cancer vascularization and invasion. Recently, we have reported that poorly prognostic EC had high levels of YT521, a newly defined RNA splicing protein. However, whether YT521 may similarly regulate the splicing of VEGF-A in EC is unknown. Here, we showed that EC specimens contained significantly higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Genes overrepresented in these clusters include YTHDC1, SRSF10, BLCAF1, MFSD8, and ABHD18. YTHDC1 is a nuclear protein involved in splicing cancer-causing transcripts [ 73 ] and plays a regulatory role in several cancers such as breast and prostate cancer [ 74 , 75 , 76 , 77 ]. SRSF10 is an SR protein and splicing regulator that activates splicing when phosphorylated and inhibits splicing when dephosphorylated [ 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genes overrepresented in these clusters include YTHDC1, SRSF10, BLCAF1, MFSD8, and ABHD18. YTHDC1 is a nuclear protein involved in splicing cancer-causing transcripts [ 73 ] and plays a regulatory role in several cancers such as breast and prostate cancer [ 74 , 75 , 76 , 77 ]. SRSF10 is an SR protein and splicing regulator that activates splicing when phosphorylated and inhibits splicing when dephosphorylated [ 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that the mRNA expression levels of YTHDF1, YTHDF2 and YTHDF3 were upregulated in breast cancer compared with that in normal tissues from healthy population. Although a signi cant downregulation in the expression of YTHDC1 and YTHDC2 was found in breast cancer, it has been reported that YT521 (YTHDC1) was over-expressed in endometrial carcinoma and promoted the metastatic process by regulating the mRNA splicing of VEGFA (53). Furthermore, YTHDC2 is involved in the metastasis of colon cancer by promoting the translation of HIF-1α (54).…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers investigated in this study (angiopoietin-2, EGF, IL-8, leptin, VEGFA, VEGFC, and VEGFD) have been chosen based on the association with a proinflammatory milieu, as well as with EC risks in previously published cohort and cross-sectional studies [24][25][26][27]. These seven biomarkers were analyzed by xMAP™ immunoassays, and measured in the culture medium.…”
Section: Luminexmentioning
confidence: 99%